2021
DOI: 10.1007/s42398-021-00166-w
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in satellite mapping of global air quality: evidences during COVID-19 pandemic

Abstract: There was a significant decline in air pollution in different parts of the world due to enforcement of lockdown by many countries to check the spread of the coronavirus (COVID-19) pandemic. In particular, commercial and industrial activities had been limited globally with restricted air and surface traffic movements in response to social distancing and isolation. Both satellite remote sensing and ground-based monitoring were used to measure the change in the air quality. There was momentous decline in the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
(41 reference statements)
0
8
0
Order By: Relevance
“… 2020 ). Many cities witnessed a significant drop in air pollutants in a range of 30 to 60%, owing to countrywide lockdowns (Dutta et al 2021 ). In Saudi Arabia, the COVID-19 lockdown was an advantage to the environment.…”
Section: Covid-19—impacts On the Environment Animal Health And Food S...mentioning
confidence: 99%
See 1 more Smart Citation
“… 2020 ). Many cities witnessed a significant drop in air pollutants in a range of 30 to 60%, owing to countrywide lockdowns (Dutta et al 2021 ). In Saudi Arabia, the COVID-19 lockdown was an advantage to the environment.…”
Section: Covid-19—impacts On the Environment Animal Health And Food S...mentioning
confidence: 99%
“…NASA’s various satellite image observations indicate that Western Europe, Northern China, the USA, and the Indian subcontinent experienced a noticeable improvement in air pollution during the pandemic compared to the same era in past years (Dutta et al 2021 ).…”
Section: Covid-19—impacts On the Environment Animal Health And Food S...mentioning
confidence: 99%
“…Behera et al (2021) reported that the seasonal variability of CH4 was linked to crop-residual burning, and the study defined higher CH4 values in 2021. Similarly, Dutta et al (2021) argued that the increase in CH4 over India agreed with the global rise using Sentinel-5P. However, the data gaps in their visualized analysis do not fully support their conclusion.…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…Being the 237 season for Rabi crops (i.e., wheat, barley, etc. ), the soil remains aerobic during pre-monsoon, 238 unlike monsoonal season, which favors soil methanogenesis (Dutta et al, 2021). However, the lack of data coverage in the analyzing period demands a need for an improved measurement network and focus on CH4 emissions over India.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several environmental studies revealed that restrictions on mobility during the lockdown had a positive effect on NO2 levels, even if not homogeneously across the considered spatial domains. For example, the broadly publicized data from the Copernicus Sentinel‐5P satellite (Ali, Abbas, Qamer, & Irteza, 2021; Ali, Abbas, Qamer, Wong, et al, 2021; Bar et al, 2021; Dutta et al, 2021; Muhammad et al, 2020) recorded for NO2 a sharp drop, in the range 20%–55%, during January–April 2020 compared to 2019 in many cities in China, India, Pakistan, Western Europe, and United States. With regards to Italy, Bauwens et al (2020) found the average TROPOMI NO2 column during the lockdown period in 2020 to be between 38 (± 10%) lower than during the same period in 2019 in Milan.…”
Section: Introductionmentioning
confidence: 99%